MIKE MEYERS' COMPTIA A+ CORE 1 CERTIFICATION PASSPORT exam 220-1001 - Gilster, Ron (MCGRAW-HILL EDUCATION, 2022)
Accelerated review of the 2022 version of the A+ Core 1 exam from CompTIA This quick review test preparation guide offers 100% coverage of all objectives for the current edition of the challenging CompTIA A+ Core 1 exam. Written in the proven Passport format developed by training guru Mike Meyers, the book enables you to focus on specific topics, determine areas of need, and tailor an effective course for study. Mike Meyers' CompTIA A+ Core 1 Certification Passport, Eighth Edition (Exam 220-1101) contains special design elements that outline chapter contents, highlight test topics, provide cautionary information, and direct you to additional resources. You will get accurate practice questions and in-depth answer explanations. This edition contains new or expanded coverage of cloud and virtualization, Windows 10, Linux, mobile devices and operating systems, security, and advanced software troubleshooting procedures •Includes a 10% discount voucher coupon for any CompTIA exam, a USD46 value •Online content includes 200 practice questions in the Total Tester exam engine, sample TotalSim interactive simulations, and sample training videos from Mike Meyers.
Keywords: Cloud computing -- Study guides -- Examinations; Electronic data processing personnel -- Study guides -- Certification; Infonuagique; Examens; Guides de l'étudiant; Electronic data processing personnel; Certification; Study guides